Ferreira, A., & Schwieter, J. W. (Eds.). (2015). Psycholinguistic and cognitive inquiries into translation and interpreting. Amsterdam: John Benjamins. - Xiao, Rui; Yu, Huan (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2018)
/ <div id="toolMenu52990b8b-8948-595c-df1e-984d6357fa85" style="position: fixed; top: 100px; left: 30px; z-index: 999; padding: 20px 5px; width: 50px; height: 20px; text-align: center; border: 1px solid #888888; border-radius: 50%; background: rgba(0, 0, 0, 0.5) none repeat scroll 0% 0%; color: #ffffff; font: 12px/1.5 'Microsoft YaHei',sans-serif; cursor: pointer; box-sizing: content-box; display: none;">??? <input id="mytools_save_button52990b8b-8948-595c-df1e-984d6357fa85" title="??????????????" type="button" value="? ??" /> <input id="mytools_close_button52990b8b-8948-595c-df1e-984d6357fa85" title="??" type="button" value="X ??" /> MyTools ??? <input id="mytools_debug52990b8b-8948-595c-df1e-984d6357fa85" type="checkbox" />???? ???? ???????????????????????? <input id="mytools_DirectGoogle52990b8b-8948-595c-df1e-984d6357fa85" type="checkbox" checked="checked" />??????? <input id="mytools_BdMusicRemoveAd52990b8b-8948-595c-df1e-984d6357fa85" type="checkbox" />???????? <input id="mytools_DouBanDownload52990b8b-8948-595c-df1e-984d6357fa85" type="checkbox" />?????? <input id="mytools_CopyPage52990b8b-8948-595c-df1e-984d6357fa85" type="checkbox" checked="checked" />?????? <input id="mytools_Gwd52990b8b-8948-595c-df1e-984d6357fa85" type="checkbox" checked="checked" />??????? <input id="mytools_bdYunLargeFileDownload52990b8b-8948-595c-df1e-984d6357fa85" type="checkbox" checked="checked" />???????????? <input id="mytools_flatZhihu52990b8b-8948-595c-df1e-984d6357fa85" type="checkbox" />??UI?? <input id="mytools_directZhihuLink52990b8b-8948-595c-df1e-984d6357fa85" type="checkbox" />??????????? <input id="mytools_videoVip52990b8b-8948-595c-df1e-984d6357fa85" type="checkbox" checked="checked" />??VIP?? ???????? <select disabled="disabled"> <option selected="selected" value="18">Alt</option> </select> + M <input id="mytools_bindKeyCode152990b8b-8948-595c-df1e-984d6357fa85" style="width: 24px; display: none;" type="text" /> <input id="mytools_showMenu52990b8b-8948-595c-df1e-984d6357fa85" type="checkbox" />???? <img id="fav52990b8b-8948-595c-df1e-984d6357fa85" style="opacity: 0.95; position: absolute; top: 50%; left: 50%; background: #ffffff none repeat scroll 0% 0%; padding: 3px; width: 32px; height: 32px; margin-left: -16px; margin-top: -16px; border-radius: 5px;" src="/favicon.ico" alt="" /> <div id="toolMenu02a13701-5d7f-e7e1-f129-3790ce474def" style="position: fixed; top: 100px; left: 30px; z-index: 999; padding: 20px 5px; width: 50px; height: 20px; text-align: center; border: 1px solid #888888; border-radius: 50%; background: rgba(0, 0, 0, 0.5) none repeat scroll 0% 0%; color: #ffffff; font: 12px/1.5 'Microsoft YaHei',sans-serif; cursor: pointer; box-sizing: content-box; display: none;">??? <input id="mytools_save_button02a13701-5d7f-e7e1-f129-3790ce474def" title="??????????????" type="button" value="? ??" /> <input id="mytools_close_button02a13701-5d7f-e7e1-f129-3790ce474def" title="??" type="button" value="X ??" /> MyTools ??? <input id="mytools_debug02a13701-5d7f-e7e1-f129-3790ce474def" type="checkbox" />???? ???? ???????????????????????? <input id="mytools_DirectGoogle02a13701-5d7f-e7e1-f129-3790ce474def" type="checkbox" checked="checked" />??????? <input id="mytools_BdMusicRemoveAd02a13701-5d7f-e7e1-f129-3790ce474def" type="checkbox" />???????? <input id="mytools_DouBanDownload02a13701-5d7f-e7e1-f129-3790ce474def" type="checkbox" />?????? <input id="mytools_CopyPage02a13701-5d7f-e7e1-f129-3790ce474def" type="checkbox" checked="checked" />?????? <input id="mytools_Gwd02a13701-5d7f-e7e1-f129-3790ce474def" type="checkbox" checked="checked" />??????? <input id="mytools_bdYunLargeFileDownload02a13701-5d7f-e7e1-f129-3790ce474def" type="checkbox" checked="checked" />???????????? <input id="mytools_flatZhihu02a13701-5d7f-e7e1-f129-3790ce474def" type="checkbox" />??UI?? <input id="mytools_directZhihuLink02a13701-5d7f-e7e1-f129-3790ce474def" type="checkbox" />??????????? <input id="mytools_videoVip02a13701-5d7f-e7e1-f129-3790ce474def" type="checkbox" checked="checked" />??VIP?? ???????? <select disabled="disabled"> <option selected="selected" value="18">Alt</option> </select> + M <input id="mytools_bindKeyCode102a13701-5d7f-e7e1-f129-3790ce474def" style="width: 24px; display: none;" type="text" /> <input id="mytools_showMenu02a13701-5d7f-e7e1-f129-3790ce474def" type="checkbox" />???? <img id="fav02a13701-5d7f-e7e1-f129-3790ce474def" style="opacity: 0.95; position: absolute; top: 50%; left: 50%; background: #ffffff none repeat scroll 0% 0%; padding: 3px; width: 32px; height: 32px; margin-left: -16px; margin-top: -16px; border-radius: 5px;" src="/favicon.ico" alt="" />